Efektivitas Debat Kandidat sebagai Media Komunikasi Politik dalam Meningkatkan Elektabilitas: Analisis Survei Pasca Debat Capres 2024 - Saeful imam; Marim Purba (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
Candidate debates are one of the key instruments of political communication that play a strategic role in shaping public opinion and influencing voters’ political choices. This study aims to analyze the effectiveness of the 2024 presidential candidate debate as a medium of political communication in increasing candidate electability. The research employs a quantitative approach using a survey technique involving 250 respondents who watched the debate either directly or through mass media. Data were analyzed using descriptive statistics and Pearson correlation tests to measure the relationship between perceptions of debate performance and changes in electoral preference. The findings show a significant positive correlation between positive perceptions of debate performance and an increase in electability. The most influential elements include issue mastery, clarity of political message delivery, and non-verbal communication gestures. These findings highlight the importance of candidate debates as an effective political communication tool in shaping public perception and strengthening electoral support.